The Phonological Deviations: An Error Analysis of the Indonesian EFL Learners’ Pronunciation - Andestopano, Abellio; Datuk, Zulfakhri Dt Majo (Vivid: Journal of Language and Literature, 2024)
The phonological deviation refers to the deviation of the phonological system from the target language norms. This research aims to reveal the causes of deviations in English pronunciation produced by the English college students’ pronunciation. The phonological deviations in producing consonants and vowels were discovered and their causes were revealed extensively. The results of the research were several deviations voiced consonants, voiceless consonants, short vowels, and long vowels. The phonological deviations included the change from /ʒ/ into /ʃ/*, /z/ into /s/*, /v/ into /s/*, /θ/ into /t/*, /ʃ/ into /s/*, /æ/ into /e/*, /əʊ/ into /o/*, /ɒ/ into /o/*, /u:/ into /u/*, and /i:/ into /i/*. The causes of these errors were the interlingual and intralingual factors. The interlingual factors occurred when the participants' habits in using the phonological patterns, systems, or rules prevented the participants from acquiring the correct phonological patterns or rules of the target language. On the other hand, the intralingual factors occurred when the participants did not know the phonological patterns or rules in the target language well. This research used a qualitative method. It is intended to describe and explain the participants’ ability in English pronunciation based on the recorded and collected data and facts, which are then analyzed systematically to get conclusions.